Analisis Perhitungan Harga Pokok Produksi Dengan Metode Full Costing Pada Et Veteran Pizza Pondok Aren - Azzahra, Fatimah; Rahmadhani, Tania; Novarianti, Shinta; Albidayah, Rangga Rayhan; Lestari, Tri (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Determining selling prices and preserving MSMEs' competitiveness depend heavily on accurate Cost of Goods Sold (COGS) calculations. Using a qualitative methodology, this study examines how Et Veteran Pizza Pondok Aren calculates COGS using the complete costing technique. Data was collected through documentation, interviews with business owners, and observations. The results show that the total production cost according to the business owner is IDR 31,660,000 for 1,200 pizza units with COGS per unit of IDR 26,000, while the full costing calculation produces a total cost of IDR 31,921,458 and COGS per unit of IDR 27,000. The difference of IDR 1,000 per unit is due to the internal method not including equipment depreciation costs as fixed overhead. The full costing method supporting the determination of the selling price and financial management more better with accurate calculation. The application of this method can improve the efficiency and competitiveness of MSME products. Further research is recommended to assess the long-term impact of this method on business profitability